2021
DOI: 10.3390/ijgi10090590
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Urbanization on Vegetation Dynamics in Mountainous Areas of Southwest China: Mechanism, Spatiotemporal Pattern, and Policy Implications

Abstract: As an important component of terrestrial ecosystems, the mountainous areas of southwest China are facing eco-environmental stress due to rapid urbanization. This study analyzed the vegetation dynamics during urbanization in 410 counties in the mountainous area of southwest China using trend analysis and bivariate spatial autocorrelation analysis. The results demonstrate the following: (1) The regional differences in the natural background and the stage of economic development resulted in obvious geographical h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…From the perspective of research methods, there are many common vegetation analysis methods, such as coefficient of variation [19], trend analysis [5], pixel dichotomy model [11], grey model [12], and so on. Coefficient of variation can be used to represent the spatial variability of soil and vegetation characteristics; combining coal mining and non-mining areas can determine the coefficient of variation threshold, which can distinguish the disturbance areas [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the perspective of research methods, there are many common vegetation analysis methods, such as coefficient of variation [19], trend analysis [5], pixel dichotomy model [11], grey model [12], and so on. Coefficient of variation can be used to represent the spatial variability of soil and vegetation characteristics; combining coal mining and non-mining areas can determine the coefficient of variation threshold, which can distinguish the disturbance areas [18].…”
Section: Discussionmentioning
confidence: 99%
“…That is, the stronger the disturbance of vegetation growth. The trend analysis method mainly uses linear regression and the least square method to find the optimal fitting slope of long time series data and can be used to characterize the degeneration and growth trend of vegetation [1,5,8]. It can reflect the annual variation of NDVI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional differences include the following: the carbon stock in the core area decreases throughout the entire area, and the extended area's decreasing area of carbon stock extends from the central part to the northeast; the decreasing area in the new development area is dispersed; the decreasing area in northeast Chongqing only appears in the central and western part, and the overall trend is increasing; the increase in the central and eastern part of southeast Chongqing is the most pronounced, which gradually expands to the whole region with a better ecological environment. The ecological environment has bene ted drastically in recent years as a result of ecological projects like the protection of forests in the middle and upper reaches of the Yangtze River, which have been successively identi ed in China (Peng et al, 2021), and the improvement of the ecological environment in southeast Chongqing corresponds with this trend.…”
Section: Spatial Characteristicsmentioning
confidence: 99%
“…In addition, among the anthropogenic factors, the implementation of forestry ecological projects effectively restored the regional vegetation, which was the main reason for the improvement of vegetation cover [31]. The secondary reason is the influence of urbanization, and the recent study on the characteristics of vegetation dynamics under county-scale urbanization found that the impacts of urbanization on vegetation change showed a significant spatial heterogeneity due to the differences in natural background and economic development stages and represented a "U"-shaped relationship between urbanization rate and the slope of NDVI change [32]. Although some analyses have been conducted on the impacts of climate change and human activities on the vegetation change in the SACA, there is still a lack of systematic research on the driving mechanism of this vegetation change.…”
Section: Introductionmentioning
confidence: 99%